A Retrospective Study: Characteristics and Management of Gonorrhea - Indah Purnamasari; Dwi Murtiastutik; Muhammad Yulianto Listiawan; Evy Ervianti; Rahmadewi Rahmadewi; Budiono Budiono; Astindari Astindari; Maylita Sari; Septiana Widyantari; Afif Nurul Hidayati (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Gonorrhea (GO) is a sexually transmitted infection that remains an important clinical and public health problem worldwide. Its incidence tends to increase both in males and females. Given the scale of the public health impact of GO, the selection of appropriate therapy is essential. Purpose: This study aimed to evaluate the characteristics, management, and recovery of gonorrhea patients. Methods: The research material was obtained from the medical record of gonorrhea patients at the Sexually Transmitted Infections (STI) Outpatient Clinic, Dermatology and Venerelogy Department, Dr. Soetomo General Academic Teaching Hospital, Surabaya, from January 2016 to December 2018. Result: We found 84 new GO patients (0.02%) out of the total new outpatients at the Dermatology and Venereology Department, Dr. Soetomo General Academic Teaching Hospital, Surabaya. Most of them were males (92.9%), 17–25 years age group (52.4%), unmarried (67.9%), and heterosexual (90.5%). The majority of therapy is dual therapy, was combination of doxycycline and cefixime (78%). Only 34 patients (40.5%) attended the follow-up visits, and 94.1% of them recovered, and 5.9% presented with cystitis. Conclusion: The characteristics features of GO varies in each variable. One of important to control GO is provide effective and appropriate treatment and routinely clinical and laboratories were needed control.